Zakāh as a Financial Resource for Development: Alleviating State Debt Burden and Fostering Economic Sustainability - Ahmad Asad Ibrahim; Ahmed Muhammad Alsaad; Yaqeen Hani Obiadaat (European Journal of Islamic Finance)
This study aims to explore the potential utilization of zakāh funds to meet certain developmental objectives of the state, thereby releasing its available financial resources to reduce state indebtedness. The significance of this research lies in the fact that the indirect role that zakāh can perform in reducing the state’s debt burden has not received much attention and needs further analysis to formulate a mechanism on how zakāh can play an effective role in indirectly supporting the state in reducing its indebtedness. The study employs a descriptive-analytical method to explain the reality of zakāh and assess its use as an indirect tool in reducing the state’s debt burden, drawing on classical jurisprudential sources and contemporary economic studies. The findings indicate that the state cannot be classified among those incapable of settling their debts, as the eligible recipients in this category are individuals. However, the study suggests including infrastructure projects and military spending under the categories of spending in the cause of Allah and on stranded travellers. This approach could alleviate the state's burden in these areas and free up financial resources to reduce indebtedness.